2016
DOI: 10.1007/s11145-016-9677-1
|View full text |Cite
|
Sign up to set email alerts
|

Diacritics improve comprehension of the Arabic script by providing access to the meanings of heterophonic homographs

Abstract: The diacritical markers that represent most of the vowels in the Arabic orthography are generally omitted from written texts. Previous research revealed that the absence of diacritics reduces reading comprehension performance even by skilled readers of Arabic. One possible explanation is that many Arabic words become ambiguous when diacritics are missing. Words of this kind are known as heterophonic homographs and are associated with at least two different pronunciations and meanings when written without diacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In other words, the learners who used the vowelized textbook always read vowelized words more accurately than un-vowelized words, which is congruent with previous studies (Abu-Hamour et al, 2013;Abu-Rabia, 1997, 1999Maroun & Hanley, 2017;Seraye, 2004). This benefit of reading with diacritics was consistent with the goal for the historical development of the diacritics system in Arabic orthography, which aimed to improve accuracy and comprehension when reading Arabic texts (Alhamad, 1982;Alhassan, 2003;Framawi, 1978;Ismaeel, 2001;Jumʻah, 1967;Sharshal, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In other words, the learners who used the vowelized textbook always read vowelized words more accurately than un-vowelized words, which is congruent with previous studies (Abu-Hamour et al, 2013;Abu-Rabia, 1997, 1999Maroun & Hanley, 2017;Seraye, 2004). This benefit of reading with diacritics was consistent with the goal for the historical development of the diacritics system in Arabic orthography, which aimed to improve accuracy and comprehension when reading Arabic texts (Alhamad, 1982;Alhassan, 2003;Framawi, 1978;Ismaeel, 2001;Jumʻah, 1967;Sharshal, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Taha (2016a) suggested that vowelization caused a visual load and could be considered redundant information for native speakers. Maroun and Hanley (2017) conducted two experiments to investigate whether diacritics improved the comprehension of all written words and whether the effects were confined to heterophonic homographs. The results of one experiment showed diacritics significantly increased the accuracy of the participants' semantic decisions about ambiguous words, but no effects for diacritics were found on unambiguous words.…”
Section: Arabic L1 Research On Diacriticsmentioning
confidence: 99%
“…The Iqra textbook's simple design that minimized visual crowding by leaving space between letters and words and included few images helped students focus on the text on each page (Chung, 2002;Zhu et al, 2016;Levi, 2008). Keeping the harakat in the text also trained the students to recognize words more accurately (Maroun & Hanley, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though short vowels are often predictable in Arabic and other Semitic languages, omitting them causes many words to become homographic which can slow down the reading speed (Abu-Rabia, 2001; Abu-Rabia, 1999; Taha, 2013). Adding harakat back to text can increase reading speed (Maroun & Hanley, 2017). To predict successfully, readers must know Modern Standard Arabic (MSA) well.…”
Section: Gulf Education and Social Policy Review Elisabeth Wilson Et Almentioning
confidence: 99%
“…-Thoughts on Arabic script's fault tolerance A script -be it a writing system or a cultural or programming script -has a certain fault tolerance beyond which it cannot be recognized or understood anymore. Scientific approaches can measure this tolerance in a particular case, like word recognition in Arabic (Maroun and Hanley 2017). What I am interested in, though, are the social, cultural, and religious conditions for handling errors.…”
Section: Some Notes On Arabic As a Writing Systemmentioning
confidence: 99%